The Influence of Service Quality, Price Fairness, Physical Environment on Patient Loyalty with Patient Experience as an Intervening Variable at Nuraida Hospital - Putri, Mulia Rachmiaty; Ruswanti, Endang; Ramadhan, Yanuar (Formosa Journal of Science and Technology, 2024)
This research aims to analyze the influence of service quality, price fairness, physical environment on patient loyalty with patient experience as an intervening variable at Nuraida Hospital. This research uses a quantitative analysis method with a cross sectional research design, the analysis tool used is SEM AMOS. The sample calculation using purposive sampling was 178. The variables in this research were service quality, price fairness, physical environment, patient loyalty and patient experience. The research uses a questionnaire as a research instrument with a 4-level Likert scale measurement. The research results show that there is a simultaneous, direct or indirect (mediated) influence of service quality, price fairness, physical environment on patient experience and patient loyalty of the Ob-Gyn Polytechnic at Nuraida Hospital.